Reasonable water management shift via Sefficiency in Sequity - Haie, Naim (2024)
It is urgent to transform management of water use systems towards sustainability, fairness and no significant harm by systemically answering the subsequent essential questions. How to comprehensively integrate the six central perspectives – adaptation/mitigation, supply/demand, descriptive/performance? How to quantify input/ output (I/O) differentials along the three pillars (water quantity, quality, benefits/values)? How to integrate and quantify sustainable equity (Sequity), sustainable I/O efficiencies (Sefficiency), conservation, and impact differentials at different levels? How to make reasonable judgements in decision-making processes? Current water management frameworks fail to present good-enough responses to these foundational questions, contrary to the complex and novel shift outlined here.